Association of Higher Intake of Plant-Based Foods and Protein With Slower Kidney Function Decline in Women With HIV - Banerjee, Tanushree; Frongillo, Edward A; Turan, Janet M; Sheira, Lila A; Adedimeji, Adebola; Wilson, Tracey; Merenstein, Daniel; Cohen, Mardge; Adimora, Adaora A; Ofotokun, Igho; Metsch, Lisa; D'Souza, Gypsyamber; et al. (Journal of acquired immune deficiency syndromes (1999), 2023)
We investigated whether there exists an association between dietary acid load and kidney function decline in women living with HIV (WLWH) receiving antiretroviral therapy (ART). One thousand six hundred eight WLWH receiving ART in the WIHS cohort with available diet data and a baseline estimated glomerular filtration rate (eGFR) ≥15 mL/minute/1.73 m2. A brief dietary instrument conducted from 2013 to 2016 under the Food Insecurity Sub-Study was used for assessing fruits and vegetables (FV) and protein intake. A mixed-effects model with random intercept and slope was used to estimate subjects' annual decline rate in eGFR and the association between FV intake and eGFR decline, adjusting for sociodemographics, serum albumin, comorbidities, time on ART, ART drugs, HIV markers, and baseline eGFR. We evaluated whether markers of inflammation mediated the effect of FV intake on decline in eGFR, using causal mediation analysis. We found a dose-response relationship for the association of FV intake and eGFR decline, with lesser annual decline in eGFR in the middle and highest tertiles of FV intake. An increase of 5 servings of FV intake per day was associated with a lower annual eGFR decline (-1.18 [-1.43, -0.94]). On average, 39% of the association between higher FV intake and slower eGFR decline was explained by decreased levels of inflammation. Plant-rich diet was associated with slower decline in kidney function. Inflammation is a potential path through which diet may affect kidney function. The findings support an emerging body of literature on the potential benefits of plant-rich diets for prevention of chronic kidney disease.